Economic analysis of egg production in replacing essential amino acids and soybean seed with meat and bone meal in layer rations of exotic chickens - Mekete, Berhane; Engida, Tesfaye; Nigussie, Helen; Kaba, Dereje (Ethiopian Journal of Science and Technology, 2025)
The study was conducted to evaluate the economic analysis of egg production by replacing essential amino acids and soybean seed with meat and bone meal in layer rations of exotic chickens. Ninety Bovan-brown layer hens were randomly selected and allocated to three dietary treatments with two replications using completely randomized design; 15 layers were allocated per replicate. The three dietary treatments were as follows: T1 (control), in which chickens were fed commercial layer ration; T2, in which chickens were fed formulated layer ration with the inclusion of essential amino acids and roasted soybean seeds; and T3, in which chickens were fed formulated layer ration with the inclusion of 10% meat and bone meal. The chickens were fed ad libitum for 90 days and the data of feed intake and egg production were recorded for 3 months. Besides, prices of different feed ingredients and commercial layer rations and egg selling prices were taken in July 2020 and February 2024. The economics of egg production were determined using a partial budget analysis that took into account the link between feed intake and egg output. Data were analysed using SAS software package. The treatment means were separated using Tukey’s Studentized Range Test. According to the economic analysis of July 2020 and February 2024, T1 had the highest (p<0.001) total gross returns per hen per 90 days (Birr) and followed by T3 while it was the least (p < 0.001) in T2. Besides, both the control and T3 had higher net return (p < 0.001) per hen per 90 days (Birr) than treatment T2. Therefore, it is concluded that alternative and economical layer ration could be formulated with the inclusion of 10% meat and bone meal along with other feed ingredients in layer rations of exotic chickens without using essential amino acids and soybean seed.